Effect of the HamSprint Drills training programme on lower limb neuromuscular control in Australian football players - Cameron, M. L.; Adams, R. D.; Maher, C. G.; Misson, D. (Journal of Science and Medicine in Sport, 2009)
This study examined the effect of the HamSprint Drills training programme and conventional football practice warm-up on lower limb neuromuscular control. The purpose-built active movement extent discrimination apparatus was used to assess lower limb neuromuscular control in 29 footballers from one professional Australian Football League club. Without vision of the contact point, participants performed 40 backward swing movement trials with each leg and made a judgment of the magnitude of each movement. Scores representing the ability to discriminate between different movement extents were calculated as the area under the player`s receiver operating characteristic curve, constructed using non-parametric signal detection theory methods. Participants were randomized to either an intervention or control group that performed different procedures in the warm-up prior to football practice sessions over a 6-week period, and then were re-tested. The intervention group performed the HamSprint programme—-drills specific to the improvement of running technique, co-ordination and hamstring function. The control group performed their usual warm-up of stretching, running, and increasingly intense football drills. Backward leg swing extent discrimination was significantly better in players following the 6-week HamSprint programme when compared to discrimination scores of players who performed their usual practice warm-up only. Significant improvement was observed in lower limb neuromuscular control in movements similar to the late-swing early stance phase of running. The HamSprint programme can therefore improve control in a specific aspect of sensorimotor system performance, and this may be useful particularly in athletes who have lower function levels or those deemed at risk of hamstring injury.